(untitled) (Research, Society and Development, 2022)
Objective: Evaluate the epidemiological profile of Covid-19 victims in Sergipe in the year 2020 to September 2021. Methods: This is an epidemiological survey based on deaths notified by Covid-19 in the state of Sergipe in the year 2020 to September 2021. Data were collected through the epidemiological bulletins of the Epidemiological Surveillance of the State of Sergipe, available to the public through the website of the State Health Department. 543th Epidemiological Report, made available on October 1, 2021, was analyzed. Results: Between 2020 and August 2021, 278,134 confirmed cases of the disease and 6,010 deaths were reported. The sociodemographic profile of the confirmed cases were mostly young people aged between 20 and 39 years, brown males. About the Clinical profile, in most cases they were people without comorbidities, followed by chronic heart disease. The lethality rate, on the other hand, affected mostly elderly, female browns. Conclusion: The predominant age group in the state was young adults between 20 and 39 years old, female, brown race, with comorbidity of arterial hypertension, thus being the most affected by the disease.